2013
DOI: 10.1017/s002221511300306x
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral sudden sensorineural hearing loss: review

Abstract: The presentation of bilateral sudden onset sensorineural hearing loss is a medical emergency requiring thorough and urgent investigation to exclude life-threatening and reversible conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
65
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 98 publications
1
65
1
1
Order By: Relevance
“…1 However, the aetiology of hearing loss following spinal anaesthesia is not yet fully understood. It is suggested that CSF leakage after dural puncture causes a decrease in intracochlear pressure and a relative increase in endolymphatic pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 However, the aetiology of hearing loss following spinal anaesthesia is not yet fully understood. It is suggested that CSF leakage after dural puncture causes a decrease in intracochlear pressure and a relative increase in endolymphatic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…1 Possible causes include viral infections, trauma, neurological diseases and neoplasia. 1 Spinal anaesthesia is one of the most widely used regional anaesthesia techniques. Sudden bilateral hearing loss occurring after spinal anaesthesia has only been reported in a few cases in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Although unilateral SSNHL is common with a relatively good prognosis, bilateral SSNHL is rare, representing less than 5% of cases, and typically has a poor prognosis with high morbidity and mortality 5. It is associated with serious systemic conditions such as toxins, neoplasms, vascular events, autoimmune diseases, infections, and iatrogenic causes 5.…”
Section: Discussionmentioning
confidence: 99%
“…It is associated with serious systemic conditions such as toxins, neoplasms, vascular events, autoimmune diseases, infections, and iatrogenic causes 5. Some authors report that SSNHL can be an early warning sign of impending vertebrobasilar ischemic stroke2 4 6 in which the incidence of hearing impairment is 1.2–14.3% 1 4.…”
Section: Discussionmentioning
confidence: 99%
“…Two assess variously the controversial topic of sub-total tonsil surgery 1 and the rare but devastating condition of bilateral sudden onset sensorineural hearing loss. 2 The third is perhaps the most extensive review to date of the epidemiology of chronic otitis media in Australian Indigenous children. 3 Rhinology research dominates the original research section, with papers looking at irrigation bottle contamination, 4 patients' perception of which side of the nose is blocked, 5 and the positive and negative aspects of home-made nasal irrigation solutions.…”
mentioning
confidence: 99%